Xung đột mối quan hệ và hành vi chia sẻ kiến thức: Vai trò điều tiết của lãnh đạo định hướng kiến thức - Nguyễn Thị Hằng , Nga; Nguyễn Kim, Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Knowledge sharing plays a crucial role in enhancing an organization’s competitive advantage. However, for various reasons, employees may be reluctant to engage in the knowledge-sharing process. Relationship conflict among individuals is a common phenomenon in the workplace; yet, its impact on knowledge-sharing behavior has not been comprehensively studied. The objective of this research is to assess the influence of relationship conflict on employees’ knowledge-sharing behavior while exploring the moderating role of a knowledge-oriented leadership style in this relationship. The study utilized a survey sample of 202 employees in the banking sector, which is a knowledge-intensive industry. SmartPLS software was employed to analyze both the measurement model and the structural model. The findings indicate that relationship conflict negatively affects employees’ sharing behavior for both tacit and explicit knowledge. Notably, knowledge-oriented leadership style was identified as an effective factor in mitigating the negative impact of relationship conflict on explicit knowledge-sharing behavior. Based on these findings, the study provides managerial implications for fostering knowledge-sharing behavior within organizations.